Rhymes of the Rockies - Whilt, James W. (Salt Lake City, UT : Project Gutenberg, 2016)
"Rhymes of the Rockies" by James W. Whilt is a collection of poetry written in the early 20th century. This book reflects the author's deep connection to the Rocky Mountains, as it portrays the beauty and solitude of nature through verses inspired by his life as a timber cruiser, packer, trapper, and guide. The poems celebrate the wonders of the wilderness, capturing the essence of outdoor life and the timeless relationships between man and nature. In this collection, Whilt shares a variety of poems that evoke vivid images and emotions related to life in the Rocky Mountains. From the adventures of hunting and trapping to contemplations of memory and nature, each poem encapsulates a different facet of mountain life. The author mourns the passing of traditional ways, such as ranching and trapping, while also cherishing the simple joys found in nature's beauty. Themes of nostalgia, love for the outdoors, and the passage of time permeate the work, inviting readers to connect with their own experiences in nature and reflect on the impact of the changing world. Overall, the book serves as a heartfelt tribute to the Rocky Mountains and the spirit of adventure that they inspire. (This is an automatically generated summary.)
Release date is 2016-08-31
Produced by Al Haines
Keywords: Rocky Mountains -- Poetry